Uneven age effects of [18F]FP-CIT binding in the striatum of Parkinson’s disease - Lee, Chong S.; Kim, Su-Jeong; Oh, Seung Jun; Kim, Hye Ok; Yun, Sung-Cheol; Doudet, Doris; Kim, Jae Seung (Annals of nuclear medicine, 2014)
Objective Dopamine transporter (DAT) imaging shows age-related decline of ligand binding in the normal striatum, a decline attributed to regulatory changes. We investigated if similar changes occur in the striatum of Parkinson’s disease (PD) patients, using PET and [ 18 F]FP-CIT, a ligand for DAT. Methods We performed [ 18 F]FP-CIT PET in 39 drug-naïve, de novo PD patients (age 56.0 ± 11.6 years, mean ± SD) and 34 healthy control subjects (age 52.3 ± 17.8). Parkinsonism was assessed by UPDRS III and Purdue pegboard. Binding ratios of [ 18 F]FP-CIT were obtained in the putamen and caudate using the occipital cortex as reference. Results Mean [ 18 F]FP-CIT binding ratios in PD were 3.76 ± 0.74 (mean ± SD) in the putamen and 6.80 ± 1.05 in the caudate nucleus, significantly smaller than those in the healthy control (9.20 ± 1.38, 8.66 ± 1.12, respectively; p < 0.001 vs. healthy control for both). Regression analysis of [ 18 F]FP-CIT binding ratios on age in healthy subjects showed significant correlations in the putamen ( p < 0.001) and caudate nucleus ( p < 0.001). Similar analysis in PD patients also showed significant correlations in the putamen ( p = 0.015) and caudate nucleus ( p = 0.018). The slope of regression in the putamen was −0.061 in the healthy control and −0.017 in PD, with significant differences between the two groups ( p = 0.0003). In contrast, the regression slope in the caudate nucleus was −0.040 in the healthy control group, and −0.032 in the PD group with no significant differences between the two groups. Conclusions Striatal [ 18 F]FP-CIT binding showed significant age affects in patients with de novo PD after standardization for the severity of disease. The age effects were significantly smaller in PD patients than those in healthy subjects, but only in the putamen, not in the caudate nucleus. Given that age-related attrition of DA neurons is even in normal striatum, the uneven age effects in the parkinsonian striatum are likely to reflect the superimposition of disease-driven compensation on the aging effect.